PENETEPAN TERHADAP BATAS USIA DEWASA MENURUT PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Tri Minarti (Universitas Kapuas Sintang, 2023)
Setting the age limit for a person is important because it will determine whether or not a person is legal to take a legal action and a person's ability to take a legal action. In the laws and regulations there is a stipulation of 18 years and 21 years. The purpose of this study is to determine the determination of the age limit according to the laws and regulations in Indonesia. This research method uses normative law approach legislation, supported by secondary data by collecting literature study data using qualitative descriptive analysis.The conclusion is the determination of the age limit for adulthood, namely 18 years and 21 years. As for efforts to overcome the diversity of maturity arrangements, the publication of Circular Letter Number 7 of 2012 concerning the Legal Formulation of the Results of the Supreme Court Plenary Meeting. Society does not feel ambiguous about the age limit of adulthood.